Contextual Factor Affecting Health Quality among Female Prisoners in Semarang - Alvy Nur Hidayati; Hermanu Joebagyo; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: Health law number 36 of 2009 article 4 states that everyone has the right to be healthy. The right applies to all people, including the prisoners even though they have broken the law. This study aimed to describe the quality of health of female prisoners in obtaining health services during detention in Semarang's female prison.Subjects and Method: This was a qualitative study with a single fixed case study research strategy. The study was conducted in November 2018. The key informants were 4 female prisoners, 1 health policlinic doctor, and 1 head of a correctional institution.Results: There was a polyclinic unit that provided health services. Prisoners were not sure that health services are often given drugs that do not provide benefits optimally. Health personnel are always prepared to provide health services outside of working hours even though the number of health personnel is limited. Referral is done by conducting a basic examination to obtain an initial diagnosis to determine the next action, referral is done with the permission of members of the correctional observer team (TPP) and the head of the prison then referral can be done at facilities that have collaborated and have MOUs with prison so that prisoners do not pay for treatment. The availability of food and beverages consumed is provided in sufficient quantities. The availability of sports facilities to support health, as well as maintaining personal hygiene of prisoners is carried out by bathing, washing clothes, cleaning beds, and disposing of sanitary napkins in the places provided.Conclusion: The lack of health personnel causes sub-optimal health services. The lack of effectiveness of the drugs causes convictions of prisoners with health services provided in prisons.Keywords: quality of health, female prisonersCorrespondence: Alvy Nur Hidayati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami No. 36 A, Surakarta, Central Java. Email: alvynurhidayati@gmail.com. Mobile: 081328353336Journal of Health Policy and Management (2019), 4(1): 1-12https://doi.org/10.26911/thejhpm.2019.04.01.01